2021
DOI: 10.3390/pharmaceutics13020168
|View full text |Cite
|
Sign up to set email alerts
|

MPC Polymer Promotes Recovery from Dry Eye via Stabilization of the Ocular Surface

Abstract: The polymer that includes 2-methacryloyloxy ethyl phosphorylcholine (MPC) is well-known as an effectively hydrating multifunction agent. In this study, we prepared an MPC polymer (MPCP) using radical polymerization with co-monomers—MPC/Stearyl Methacrylate/N,N-dimethylacrylamide—and evaluated the MPCP’s usefulness for dry eye treatment using a rabbit model treated with N-acetylcysteine. The MPCP particle size was 50–250 nm, and the form was similar to that of micelles. The MPCP viscosity (approximately 0.95 mP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…7 b, p(MPC) exhibited a reduction ( p < 0.05) in fluorescein staining score after h12 of administration. The instillation of hydrophilic p(MPC) can replenish moisture on the ocular surface and stabilize the osmolarity of tear film [ 25 ], but did not adhere well and did not produce an anti-oxidative action to inhibit the progression of DED. Hence, without sufficient bioavailability and bio-adhesive mechanism, CsA and p(MPC) groups have similar scores to those for the untreated DED model (Ctrl) at 4 days postoperatively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 b, p(MPC) exhibited a reduction ( p < 0.05) in fluorescein staining score after h12 of administration. The instillation of hydrophilic p(MPC) can replenish moisture on the ocular surface and stabilize the osmolarity of tear film [ 25 ], but did not adhere well and did not produce an anti-oxidative action to inhibit the progression of DED. Hence, without sufficient bioavailability and bio-adhesive mechanism, CsA and p(MPC) groups have similar scores to those for the untreated DED model (Ctrl) at 4 days postoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…10 a, all polymer samples demonstrate an increase in tear volume after a h12 topical treatment. Nagai and colleagues showed that p(MPC) can enhance corneal water retention, increase tear volume, and prolong tear film break-up time without increasing the total mucin content in the tear film of a normal rabbit [ 25 ]. The tear meniscus height of p(MPC) and other copolymer groups were ≥ 0.21 mm (more prominent than Ctrl and CsA groups at 0.17 mm) at h12 postoperatively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MPC polymer enhanced the volume of tear fluid in animal models of DED [Nagai 2021]. To date, soft contact lenses containing this MPC have been approved by the Food and Drug Administration (FDA) [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Issues such as crosslinking techniques, crosslinking chemical additives, and factors influencing crosslinking success including immunogenicity and toxicity are discussed, as well as the limitations and prospects of crosslinking strategies in this field. The research article by Nagai N. et al [6] present a novel biopolymer (MPCP) with hydrating properties that helps to normalize the tear film in an animal model of the severe immune-based, inflammatory disorder that impairs the homeostasis of the ocular surface known as dry eye disease. Using a specific polymerization procedure, MPCP polymer enhanced tear film volume and prolonged the tear film breakup time in disease animal, indicating promising therapeutic properties.…”
mentioning
confidence: 99%